Children with chronic illnesses: factors influencing family hardiness*. (March 2015) - Woodson, Kenneth D.; Thakkar, Sunny; Burbage, Michelle; Kichler, Jessica; Nabors, Laura
<x xml:space="preserve">Abstract</x> The current study assessed factors related to family hardiness in families of children coping with medical procedures related to a chronic illness. Participants were 68 parents of children with chronic illnesses, who were receiving complex medical treatment at a local hospital. Parents completed a scale assessing family hardiness and a semi-structured interview assessing their positive and negative coping strategies and those of their child. A linear regression analysis was used to examine the relationship between several predictors, including child age, number of medical conditions for the child, family income, number of positive and negative parent and child coping strategies, and family hardiness (outcome variable). Results indicated that parents of older children and children who exhibited negative coping strategies reported lower family hardiness. Older children may have had their chronic illness for a longer period of time, which could be wearing for the children and their families. Results of this study suggested that negative child coping may have deleterious effects on the family, and nurses and other health professionals should provide ideas for positive child coping and consider collaboration with mental health providers when they identify children facing emotional problems.